Message Security Using a Combination of Hill Cipher and RSA Algorithms - Yogi Suryo Santoso (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
The process of exchanging digital messages is increasingly being used due to its easy and practical use. But the process of exchanging digital messages is vulnerable to being tapped by unauthorized people. Cryptography is the study of mathematical techniques related to aspects of information security, such as data confidentiality, data validity, data integrity, and data authentication. With cryptography, the process of exchanging messages between two people can be done securely. Thus, cryptographic techniques are used to overcome security issues when exchanging messages. The methods used in this study are hybrid hill cipher and RSA cryptography. In this study it was shown that hybrid hill cipher cryptography with a 3x3 matrix key and RSA with a 512 bit key can overcome security issues when exchanging data so that messages sent cannot be read by unauthorized people.